MARKET MICROSTRUCTURE THEORY: FIXED EFFECT MODEL APPROACH ON COMPANY FUNDAMENTALS PROFITABILITY - Devi, Wiara Sanchia Grafita Ryana; Arfiansyah, Ferry; Pranata, Rengga Madya; Damaianti, Indriana; Kharisma, Mita (Jurnal Signaling, 2024)
The concept of market microstructure, or market microstructure theory, examines the dynamics behind the formation of stock prices in Indonesia. There are three primary categories that may be used to categorize the many explanations offered by academics and researchers on the processes that lead to the establishment of stock prices on the Exchange. In this work, a quantitative methodology is utilized to evaluate hypotheses and confirm market microstructure theory, and signal theory. This research makes use of secondary data, namely information gleaned from the Indonesia Stock Exchange for the years 2017-2020. The data in question cover the period of time. The State-Owned Enterprises (BUMN) group, of which the research sample is a member, provides the sample for this study. The findings of the study indicate that there is a connection between fundamentals and profitability.